Literary seduction: Minds, bodies and non-textual phenomena - Michael BURKE (E-REA)
Deliberations into what makes a literary text persuasive, what seduces readers to continue reading once the act of reading started, is often a combination of (a) what is written (the themes), (b) the order and manner in which the events of the story are presented (the narrative structure and how the text is filtered, and (c) how a story is written (the style and rhetoric of the text). But arguably these factors alone cannot seduce a reader into continuing to read if a number of mind/body, non-textual phenomena are not in alignment. Evidently, there must be an inner, axial (textual) layer and a much less attended to outer, auxiliary (non-textual) layer of seduction at work during engaged acts of literary reading, both of which must arguably be optimal if a reader is to be successfully seduced into reading - and into continuing to read. In this paper, drawing primarily on my own theory of affective inputs during literary reading and the literary reading loop within the framework of the oceanic literary reading mind (Burke 2011), I will discuss a number of such outer-layer, auxiliary, non-textual phenomena, namely, (i) mood, (ii) medium, and (iii) location. I will argue that in order to fully understand why readers continue to read a work of fiction, one must be aware of all the dimensions of literary seduction: both the textual and non-textual. In the embodied, cognitive age of text processing that we now find ourselves in, it would be remiss of us to continue to focus solely on the axial, textual features of story comprehension at the expense of auxiliary, non-textual phenomena.